2020
DOI: 10.1038/s41598-020-75135-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolomic investigations in vitiligo patients

Abstract: Urinary metabolomics is a useful non-invasive tool for large-scale screening of disease-related metabolites. However, no comprehensive urinary metabolomic analysis of vitiligo is presently available. To investigate the urine metabolic pattern of vitiligo patients, we conducted a combined cross-sectional and prospective self-control cohort study and an untargeted urinary metabolomic analysis. In the cross-sectional study, 295 vitiligo patients and 192 age‐ and sex‐matched controls were enrolled, and 71 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…A comprehensive vitiligo map with 4845 protein nodes linked with 107,416 edges revealed a list of top-order proteins that play a key role in the disease pathology mechanism including SUMO2, ESR1, COPS5, MYC, SMAD3, and Cullin proteins (Malhotra et al, 2018). The need for a useful non-invasive tool for large-scale screening, urinary metabolomics was recently reported to detect disease-related metabolites using (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive vitiligo map with 4845 protein nodes linked with 107,416 edges revealed a list of top-order proteins that play a key role in the disease pathology mechanism including SUMO2, ESR1, COPS5, MYC, SMAD3, and Cullin proteins (Malhotra et al, 2018). The need for a useful non-invasive tool for large-scale screening, urinary metabolomics was recently reported to detect disease-related metabolites using (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for ARA decrease is still unclear. We surmise that metabolic exhaustion might provide an explanation considering the reportedly elevated levels of PGs (PGE2, PGD2 and PGF2α) in vitiligo lesions and leukotrienes in urine ( 11 , 13 ), which are both metabolites of ARA. It’s worth noting that abnormality of phospholipase in patients with vitiligo has not been previously reported, which needs further study.…”
Section: Discussionmentioning
confidence: 91%
“…Metabolomics is an emerging field that be used to monitor the alternations in all low molecular metabolites produced by cellular processes, which delineates an overall metabolic profiles have widely applicable to investigate clinical features of various diseases. Recently, the metabolome based on miscellaneous samples, including serum, plasma, blister liquid and urine so on, have revealed that metabolic disturbance of amino acids and lipid mediators are involved in physiological and pathological changes in vitiligo patients (10)(11)(12)(13). However, almost all previous studies on the basis of non-targeted metabolomics techniques, which the accuracy of quantitative methods are necessary to promote further.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant altered metabolite was L-alpha-aminobutyric acid (VIP = 3.91, FC = 3.68), which was involved in cysteine and methionine metabolism, and we showed it was unregulated in SL patients compared to SNL patients. The abnormal cysteine and methionine metabolism was also observed in vitiligo patients compared to HC by Liu et al 22 It was reported that aberrant homocysteine metabolism may lead to increased oxidative damage, excessive IL-6 production, and then trigger autoimmunity and the development of vitiligo. 23 , 24 Likewise, excessive oxidative damage was also a characteristic of SLE.…”
Section: Discussionmentioning
confidence: 91%